The Experience of Women with Handicaps in 21st Century Archival Projects - Munévar M., Dora Inés (2011)
This article is an analysis of the way 21st century archival projects could work to benefit the reconstitution of silenced subjectivities and uncover histories of exclusion. The case chosen for analysis is the documentation of women with handicaps in rehabilitation, mental health, and legal protection institutions. On that basis the author proposes mechanisms for information deposited in the archives, especially institutional, to contribute to the recovery of memory and to the democratization and decolonization of the history of excluded and marginalized groups. This, thanks to the fact that archives house not only authorized written documents but also a multiplicity of oral and visual materials. These materials could contribute to the visibility and recognition of difference, from the experiences lived, for example, by women with handicaps who would in this way acquire their own voice.